PENGARUH MODEL PEMBELAJARAN SMALL GROUP DISCUSSION TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV - Alsha Maulinda; Erna Labudasari; Anih Sumiati (Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to determine the effect of the Small Group Discussion learning model on reading comprehension skills in class IV students at SDN 2 Setu Wetan. This research uses a quantitative type of research using the experimental method. The research design form uses Pre-Experimental Designs with the One-Group Pretest-Posttest Designs design form. Data collection techniques use observation, multiple choice pretest-posttest, interview sheets, and documentation studies. The data analysis technique uses prerequisite tests, namely normality, homogeneity, N-Gain tests and hypothesis tests, namely correlation tests, regression tests and coefficient of determination tests with the conditions that Ha is accepted and Ho is rejected. The results of this study indicate that there is a positive and significant influence between the reading comprehension abilities of class IV students at SDN 2 Setu Wetan. The results of the hypothesis test were 0.000<0.05 with a correlation level of 0.573 which was positive. With the regression test, the data showed that it was significant at 0.000<0.05, in other words the proposed hypothesis was accepted, namely Ha was accepted and Ho was rejected. The magnitude of the influence of the Small Group Discussion (SGD) learning model on students' reading comprehension abilities was 24.70%, while the rest was influenced by other factors.